People's Voyages in Remote Areas and Stakeholder Response - Alam, Kodrat (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2020)
In the country of Indonesia, whose territories are islands and waters, sea transportation is an important means of transportation for developing community interaction in various fields. Public voyage is a means of transportation that can reach archipelagic areas. In its development, currently the existence of people's voyage has been marginalized by the operation of modern ships and the policies that accompany it, so that it has suffered a downturn. In connection with this adversity, it is interesting to ask, what factors have caused it? The research was conducted using a qualitative approach, data collection was carried out through in-depth interviews, FGDs and field observations. The results showed that the marginalization of people's voyage in Central Maluku was because the existing people's voyage facilities were unable to compete with the operation of fast boats from sea transportation companies and pioneer ships (ferries) provided by the government. The existence of a port that prefers loading and unloading with machines is also a separate problem faced by public voyage, so that people's voyage is rejected because it carries out loading and unloading with human power. In addition, government policies are also a factor that is less supportive of the development of people's voyage in Maluku. Whereas people voyage in the form of small ships are still needed by the island community. Therefore, it needs good management so that people's voyage vessels remain